Pengaruh E-Service Quality dan E-Trust terhadap E-Satisfaction Pada Nasabah Pengguna Aplikasi Mobile Banki¬ng Bank Tabungan Negara Bangkalan - Andika Mubarok; Nirma Kurriwati (Management Department of Economics and Business Of Trunojoyo Madura University, 2021)
The purpose of this study was to determine whether there is an effect between e-servqual on e-satisfaction, to find out whether there is an effect between e-trust on e-satisfaction, and to find out whether e-servqual and e-trust have a joint influence on e-satisfaction on customers who use the M-Banking BTN. This study uses quantitative methods, the sampling method used is non-probability sampling. The type of data used is primary data, the data source comes from a questionnaire with a sample size of 100 respondents. The data analysis method used is multiple linear regression analysis using validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, T test and F test. (1) e-servqual has a positive and significantly on e-satisfaction, (2) e-trust has a positive and significant effect on e-satisfaction, (3) e-servqual and e-trust have a positive and significant effect simultaneously on e-satisfaction on customer application users m-banking BTN